2012
DOI: 10.18251/ijme.v14i2.506
|View full text |Cite
|
Sign up to set email alerts
|

Complicating Culturally Relevant Pedagogy: Unpacking African Immigrants' Cultural Identities

Abstract: <!--[if gte mso 9]><xml> <w:WordDocument> <w:View>Normal</w:View> <w:Zoom>0</w:Zoom> <w:TrackMoves /> <w:TrackFormatting /> <w:PunctuationKerning /> <w:ValidateAgainstSchemas /> <w:SaveIfXMLInvalid>false</w:SaveIfXMLInvalid> <w:IgnoreMixedContent>false</w:IgnoreMixedContent> <w:AlwaysShowPlaceholderText>false</w:AlwaysShowPlaceholderText> <w:DoNotPromoteQF /> <w:LidThemeOther>EN-US</w:LidThemeOt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In relation to first generation Black/African American girls, research finds that they can often feel lost, frustrated, and isolated in the United States and in school for a variety of reasons (Allen, Jackson, & Knight, 2012;Okpalaoka, 2009;Rong & Brown, 2002;Rong, & Fitchett, 2008;Waters, 1999). Some of these reasons include teachers and peers who do not understand and appreciate first generation Black/African American cultural values, practices, and identities; being made fun of by nonimmigrant peers for the way they dress or wear their hair; a curriculum that does not speak to who they are or what they know; and a dominant, U.S. perspective that holds monolithic and negative views of Black/ African American communities, despite differences within and across U.S. born and foreign-born Black/African American populations (Allen et al, 2012;Okpalaoka, 2009;Olsen, 2008;Rong & Brown, 2001Rong & Fitchett, 2008;Waters, 1999). The cognitive, social, and emotional consequences of these experiences, both in and out of school, can influence how first generation Black/African American girls develop confidence and belief in their ability to be academically successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to first generation Black/African American girls, research finds that they can often feel lost, frustrated, and isolated in the United States and in school for a variety of reasons (Allen, Jackson, & Knight, 2012;Okpalaoka, 2009;Rong & Brown, 2002;Rong, & Fitchett, 2008;Waters, 1999). Some of these reasons include teachers and peers who do not understand and appreciate first generation Black/African American cultural values, practices, and identities; being made fun of by nonimmigrant peers for the way they dress or wear their hair; a curriculum that does not speak to who they are or what they know; and a dominant, U.S. perspective that holds monolithic and negative views of Black/ African American communities, despite differences within and across U.S. born and foreign-born Black/African American populations (Allen et al, 2012;Okpalaoka, 2009;Olsen, 2008;Rong & Brown, 2001Rong & Fitchett, 2008;Waters, 1999). The cognitive, social, and emotional consequences of these experiences, both in and out of school, can influence how first generation Black/African American girls develop confidence and belief in their ability to be academically successful.…”
Section: Discussionmentioning
confidence: 99%
“…That is, it is also important to assess the variations in patterns of academic self-efficacy among different ethnicities and countries of origin. Many studies demonstrate that educational experiences vary significantly for Mexican, Haitian, Korean, Hmong, Filipino, Senegalese, and Ghanaian youths (Allen et al, 2012;Lee, 2005;Ngo, 2010;Portes & Rumbaut, 2001Suárez-Orozco & Suárez-Orozco, 2001;Teranishi, 2002;Waters, 1999). Shortcomings of this data also foreclose an examination of various educational policies such as Race to the Top and Common Core on the children of immigrants' patterns of academic selfefficacy.…”
Section: Discussionmentioning
confidence: 99%
“…She found that cultural identity has both positive and negative implications for West African immigrant youth’s educational experiences, and teachers must understand the hybrid identities of these immigrant youth. Other studies (Allen, Jackson, & Knight, 2012; Okpalaoka & Dillard, 2012) found that cultural factors had a meaningful impact on Black immigrants’ educational experiences and made recommendations that teachers who are tasked to teach these immigrant students receive professional development training and cultural knowledge about African immigrant youth. Other studies (Cone, Buxton, Lee, & Mahotiere, 2014; Fries-Britt, George Mwangi, & Peralta, 2014) found that factors such as socioeconomic status (SES), gender, racial/ethnic composition of language, generation status, school, and family largely influence the racial/ethnic identifications of Black immigrants.…”
Section: Related Literaturementioning
confidence: 99%
“…It promoted their academic achievement and social interaction. For many of the participants, club membership at school is a known factor that contributed to their civic awareness and knowledge (Allen et al, 2012). It appears that membership of social clubs in school provided opportunities for participants to share their life experiences and learn ways to adjust and adapt to new urban school environments.…”
Section: Challenges That Affect Immigrant Youth From West Africa In Tmentioning
confidence: 99%
“…Using equity pedagogies. There is considerable evidence that using equity pedagogies can support minoritized students' learning outcomes (i.e., development of conceptual knowledge, achievement, and identity development) across all content areas (Allen-Handy et al, 2020;Boaler & Sengupta-Irving, 2016;Allen et al, 2012;Tsurusaki et al, 2013). Much of this research has been conducted in English language arts (ELA; e.g., Duncan-Andrade, 2007), social studies (e.g., Stovall, 2006), early childhood education (e.g., Souto-Manning & Martell, 2017), or bilingual education (e.g., Irizarry & Antrop-González, 2007).…”
Section: Equity Pedagogies In Stem and Cs Education: If Not Now When?mentioning
confidence: 99%